2020
DOI: 10.1088/1361-648x/ab9e2d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase diagram of CrPS4 and its exchange interaction in contact with NiFe

Abstract: The magnetic phase diagram of the two-dimensional van der Waals magnet CrPS 4 and the exchange bias effect of CrPS 4 in contact with NiFe film have been investigated. Based on the magnetic measurements, we figure out the relatively low spin-flop field and spin-flip field for CrPS 4 , both of the spin transition phenomena are strongly affected by the temperature. The perpendicular exchange bias effect is studied in CrPS 4 single-crystal flake covered with 5 nm NiFe. Meanwhile, the variation of the cooling field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…At 5 K, the magnitude of H EB for a CrPS 4 /Fe 3 GeTe 2 device with a pristine interface is found to be ∼12.5 mT (±1 mT), which gradually decreases as the temperature is increased and found to be negligible (<2 mT) above 20 K, the T B of CrPS 4 as reported previously. 22 We also observed a switching of the polarity of EB from negative to positive at 15 K close to the T B , similar to the observations by S. Ding et al, where they observed switching EB behavior in pristine CrPS 4 /FeNi interface. 22 Interestingly, the observed T B for a CrPS 4 /Fe 3 GeTe 2 system is found to be 20 K, significantly lower than the T N of CrPS 4 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…At 5 K, the magnitude of H EB for a CrPS 4 /Fe 3 GeTe 2 device with a pristine interface is found to be ∼12.5 mT (±1 mT), which gradually decreases as the temperature is increased and found to be negligible (<2 mT) above 20 K, the T B of CrPS 4 as reported previously. 22 We also observed a switching of the polarity of EB from negative to positive at 15 K close to the T B , similar to the observations by S. Ding et al, where they observed switching EB behavior in pristine CrPS 4 /FeNi interface. 22 Interestingly, the observed T B for a CrPS 4 /Fe 3 GeTe 2 system is found to be 20 K, significantly lower than the T N of CrPS 4 .…”
Section: Resultssupporting
confidence: 91%
“…22 We also observed a switching of the polarity of EB from negative to positive at 15 K close to the T B , similar to the observations by S. Ding et al, where they observed switching EB behavior in pristine CrPS 4 /FeNi interface. 22 Interestingly, the observed T B for a CrPS 4 /Fe 3 GeTe 2 system is found to be 20 K, significantly lower than the T N of CrPS 4 . An estimation of the interfacial exchange coupling energy between CrPS 4 and Fe 3 GeTe 2 , calculated using a simplistic model provided by D. Mauri et al, 26 is comparable to the weaker interlayer antiferromagnetic exchange coupling (0.16 meV) in CrPS 4 .…”
Section: Resultssupporting
confidence: 91%
“…In a system with sizable DMI, Néel type domain walls are energetically favorable over the Bloch type domain walls [28]. The current-induced effective field 𝜇 0 H eff , generated by the dampinglike spin orbit torque, can drive the Néel domain wall similarly to the effect of an out-of-plane field in a direction related to the chirality of the domain wall [28], which will lead the horizontal shift of the hysteresis loops, similarly to the exchange bias field in PMA exchange bias systems [29]. Figure 1b shows the shifted hysteresis loops in the presence of a charge current of density +2.2 × 10 10 Am -2 and -2.2 × 10 10 Am -2 for a GGG / TmIG (5.4) / Pt (7) (units in nanometer) sample, where reversing the polarity of the probing current leads to a negative displacement of the out-of-plane hysteresis.…”
mentioning
confidence: 99%
“…[243] Exchange-bias effect was also found in CrPS 4 flakes covered with 5 nm NiFe. [244] Except for A-type AFMs mentioned above, MPS 3 (M = transition metal) vdW family with C-type and G-type AFM is the most studied. The primary magnetic properties have been summarized in some reviews.…”
Section: -9mentioning
confidence: 99%